STRATEGI PENGEMBANGAN PANTAI BIAS TUGEL SEBAGAI DAYA TARIK WISATA SNORKLING DAN SURFING DI DESA PADANGBAI, KECAMATAN MANGGIS, KABUPATEN KARANGASEM, BALI - I Nyoman Parta1; Ni Putu Riana Sari (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
Tourist visits to Karangasem Regency continue to increase so that it becomes a very big opportunity for Bias Tugel Beach to be further developed into a tourist attraction for snorkeling and surfing. Developed Bias Tugel Beach is able to open jobs in the tourism sector so that it can reduce unemployment in the area. This research will provide a conservation solution through preservation in the field of Strategic Management, especially the strategy for sustainable tourism development on the Bias Tugel coast. This research was conducted at Bias Tugel Beach which is based on several problems such as lack of supporting facilities, tourist attractions that only rely on the beauty of the beach, and increased security to guard tourists, and implementation of tourism development strategies that are not yet optimal. The access to Tunggel Ordinary Beach is very unfriendly, tends to be dangerous, because of the steep, slippery paths, which threaten the safety of the tourists who visit. The data analysis technique used SWOT and QSPM analysis.